MODELING OF COOPERATION TO IMPROVE RURAL ECONOMIC IN LANGKAT - Muhammad Buchari Sibuea (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Koperasi Unit Desa is a representation of public institutions should be able to become a pillar of the economy right in the rural, although currently experiencing a crisis of confidence. The research aims to improve the effectiveness and efficiency of service cooperatives in increasing the members' income. Outcomes research resulted in the cooperative model is ideal as an economic institution efficient, effective in increasing the members' income. The study was conducted in Langkat where the population are Koperasi Unit Desa’s active in the agricultural sector. The sampling technique used purposive random sampling. Research methods and development with a preliminary survey measures, planning models, test models, model validation and dissemination. Research instruments include a questionnaire, recording documents and tests. Data were analyzed by using descriptive analysis and t test. The initial stage of analysis cooperative services that match the demands of the members, then the appropriate service strategy used in the agricultural sphere. Also the analysis of the needs of members with regard to farming, so found materials to create a model for cooperative services that serve as the ideal next research materials. The results showed a success rate of cooperatives in rural economic development is influenced by many aspects such as the characteristics of the members, basic capabilities, management and performance of cooperatives. Best cooperative model is consistent with the character and potential of the community. There is a very close relationship between the aspects examined by the success rate of the cooperative. The government's role in building the economy is expected to create policies that favor the cooperatives. Build strong through Koperasi Unit Desa to exploit the potential of the community is the best way to build the economy so as to form agri-based cooperatives. The implication being offered is that in designing a development, should be implemented according to the characteristics and potential of an integrated approach to the region.Keyword : cooperative, the rural economy